2011
DOI: 10.1179/1364859411y.0000000027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TNF-α, IL-4, and IL-10 and parasite density in spleen and liver ofL. (L.) chagasinaturally infected dogs

Abstract: Dogs are the main domestic reservoirs of L. (L.) chagasi. Once in the vertebrate host, the parasite can cause visceral leishmaniasis, which can also be transmitted to humans. Cytokines are key elements of the host immune response against Leishmania spp. To investigate whether tumor necrosis factor (TNF)-a, interleukin (IL)-4 and IL-10 are associated with pattern infection in dogs, these cytokines were quantified in the spleen and liver of dogs naturally infected with L. (L.) chagasi, with or without clinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 46 publications
2
27
0
1
Order By: Relevance
“…Michelin et al . measured TNF- α , IL-4 and IL-10 in the liver and spleen of dogs naturally infected with L. infantum and reported that all cytokines studied were higher in the spleens of symptomatic dogs compared with asymptomatic or non-infected controls (Michelin et al 2011). …”
Section: Organ Specific Immune Responsesmentioning
confidence: 99%
“…Michelin et al . measured TNF- α , IL-4 and IL-10 in the liver and spleen of dogs naturally infected with L. infantum and reported that all cytokines studied were higher in the spleens of symptomatic dogs compared with asymptomatic or non-infected controls (Michelin et al 2011). …”
Section: Organ Specific Immune Responsesmentioning
confidence: 99%
“…in macrophages . IL‐10 is one of the major suppressor cytokines present in CVL, and a positive correlation between IL‐10 and parasite burden has been established . Moreover, a positive correlation between HO‐1 and IL‐10 has also been described in infected dogs, and inhibition of HO‐1 was found to increase the lymphoproliferative response of these dogs, in association with suppression of IL‐10 production .…”
Section: Introductionmentioning
confidence: 88%
“…One striking finding of this study is that there are significant correlations between the levels of antigenstimulated cIL-10 production in PBMC and RhCMV genome copy numbers detected in saliva. This is not unique to RhCMV, as cIL-10 levels have been positively associated, either alone or with other biomarkers, with increased burdens of other pathogens, including human papillomavirus, HIV, hepatitis B virus, EpsteinBarr virus (EBV), Mycobacterium tuberculosis, Leishmania spp., dengue virus, and murine and human CMV (45,(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72). While the specific cell type(s) responsible for elevated cIL-10 expression in response to RhCMV antigen exposure was not explored, multiple cell types have been implicated for other pathogens, including regulatory B and T cells.…”
Section: Discussionmentioning
confidence: 99%